CHARACTERISTICS OF BASALTIC PILLOW LAVA IN JARUM VILLAGE, BAYAT: MAGMA EVOLUTION AND PETROGENETIC MODEL - Hirawan, Aditya (2017)
Bayat Region have been recognized as fossils of tertiary volcanoes in Southern Mountains, Central Java; with volcanic bodies such as dikes, sills, pyroclastics, and lava flows. Former studies reveals there were four times of magmatisms occured in Southern Mountains which aged early Oligocene to middle Miocene. However, former studies have not proved whether the outcropped volcanic rocks are originated from the same magmatism through geochemistry study. This research is aimed to complete the previous study by comparing the bulk rock geochemistry of basaltic pillow lavas in Jarum Village, approximately 3 km to the south of Pendul Hill, with the Pendul intrusion body itself. Methods applied are bulk rock geochemistry analysis (ICP-AES) and trace elements using ICP-MS, supported by petrographic analysis. Bivariate plots constructed to show cogenetic trends between two sets of above mentioned samples, while spider diagrams are drawn showing magma origin in respect with the comparison between the abundancae of LILE towards HFSE. By geochemical meaning, Pendul gabbroic–dioritic intrusion in Jiwo Hills shows early stage of magmatism while basaltic pillow lavas in Jarum Village, as the younger-aged volcanic body, is expected to originate from the same magmatism. The expected result of this research is a cogenetic trend on bivariate plots and in AFM diagram, as well as the decrease of siderophile compatible trace elements in spider diagrams between the two sets of samples. This experiment geochemically proves the process of magma evolution and establishes petrogenetic model of Bayat magmatism in a specific scope. Keywords: bulk rock chemistry, petrography, cogenetic trend, magma evolution